Influence of technology acquisition, external technology exploitation and employee autonomy on the performance of bureaucratic organizations - Suwannasri, Isaree (International Journal of Innovative Research and Scientific Studies, 2023)
Organizations use technology to prosper in the digital and technological revolutions. The digital and technical revolution has prompted governments to adopt and use technology to provide effective services to citizens. The purpose of this research is to examine how technology acquisition, external technology exploitation, employee autonomy through open innovation and innovation performance affect bureaucratic people’s development. The researcher quantitatively distributed the questionnaire online. Four departments were chosen to collect data from 480 IT-related respondents. For hypothesis testing and correlation, the structural equation model (SEM) was used. The results demonstrated a significant relationship between technology acquisition, open innovation, external technology exploitation, innovation performance, employee autonomy, open innovation and organization performance. The research’s findings revealed that an organization's performance can be practically achieved by obtaining advanced technology, external knowledge and the skills of its personnel through open innovation which can drive innovation performance toward organizational performance. Consequently, it indicates that employees and cutting-edge IT are essential for generating new ideas for open innovation and enhancing an organization's performance. Leaders and employees must understand open innovation to maximize themselves and their organizations’ potential. In addition, the most important practical implication of this research is that implementing advanced technology, innovation and technology management that includes digital literacy can improve the performance of bureaucratic organizations.